Doubts around the division of occupational health and safety responsibilities in temporary employment - Zbucka-Gargas, Marta (Temporary employment as an atypical form of employment: No. 19/2022, 2022)
The publication addresses the issue of occupational safety in temporary employment. It discusses the liability of the parties, including issues of accidents at work and occupational diseases. In practice, these issues raise numerous doubts, but also the question arises as to whether the division of duties between two entities does not reduce the level of safety of the employed.